2020
DOI: 10.3390/jcm9082587
|View full text |Cite
|
Sign up to set email alerts
|

C1q/TNF-Related Protein-3 (CTRP-3) and Pigment Epithelium-Derived Factor (PEDF) Concentrations in Patients with Gestational Diabetes Mellitus: A Case-Control Study

Abstract: Background: Gestational diabetes mellitus (GDM) is the most common metabolic disorder in pregnant women, defined as any degree of glucose intolerance with onset or first detected during pregnancy. Explanation of its pathogenesis is extremely important due to the possibility of preventing serious maternal and fetal complications. The aim of the study was to evaluate the concentrations of two molecules: C1q/tumor necrosis factor-related protein-3 (CTRP-3) and pigment epithelium-derived factor (PEDF) which may po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…The obtained results and literature review point to a role of disturbed levels of adipocytokines and hepatokines during pregnancy in development of gestational glucose intolerance and the progress to diabetic state. This explanation supported that previously detected by Francis et al [34] and Gęca et al [35] who documented a possible role for disturbed levels of diabetogenic factors secreted by either or both of adipose tissue and hepatocytes in development of GDM.…”
Section: Discussionsupporting
confidence: 92%
“…The obtained results and literature review point to a role of disturbed levels of adipocytokines and hepatokines during pregnancy in development of gestational glucose intolerance and the progress to diabetic state. This explanation supported that previously detected by Francis et al [34] and Gęca et al [35] who documented a possible role for disturbed levels of diabetogenic factors secreted by either or both of adipose tissue and hepatocytes in development of GDM.…”
Section: Discussionsupporting
confidence: 92%
“…studied panel of adipokines; fatty acid binding protein-4, chemerin, and soluble leptin receptor and indicated a role for these adipokines in the pathogenesis of GDM with significant associations detected early in pregnancy before typical GDM screening time. Also, Gęca et al, [29] found serum concentrations of C1q/tumor necrosis factor-related protein-3, one of adipokines, were significantly higher in women with GDM, irrespective of being diet-or insulin treated or not treated at all in comparison to levels estimated in control group. Interestingly, at time of diagnosis of pregnancy, women who developed GDM were found to have significantly higher BMI than non-GDM women and statistical correlations detected a positive significant correlation between BMI at time of pregnancy diagnosis and severity of GDM as judged by 2-hr PPBG during glucose tolerance testing at 24 th GW.…”
Section: Discussionmentioning
confidence: 94%
“…These findings point to a fact that pregnancy is a diabetogenic state, but certain women were vulnerable to manifest diabetic BG levels and go in hand with Li et al [28] who found the levels of FBG, PPBGG and insulin resistance scorings were significantly higher in GDM than in normal glucose tolerance women who showed progressive increase of their FBG and PPBG but do not approach the diagnostic level of GDM. Explanation of pathogenesis of gestational glucose intolerance is extremely important, but was still indefinite [29] and Li et al, [28] attributed it to progressively declining pancreatic β-cell function as manifested by increased insulin resistance scorings. As another explanation, disturbed levels of adipokines, which are secreted by adipose tissue, during pregnancy may play an important role in pathogenesis of gestational hyperglycemia, insulin resistance and progression to GDM.…”
Section: Discussionmentioning
confidence: 99%
“…In extravillous trophoblast cells, hypoxia induces overexpression of PEDF, which is associated with increased apoptosis and decreased invasiveness that may be implicated in placental defects in PE [119]. It has been observed that PEDF concentrations are higher in women with GDM than in controls and significantly predict the development of DM2 at 3 months postpartum [120]; however, another study reports no difference in PEDF concentrations between women with GDM and controls [121].…”
Section: Perspectives On the Study Of Adipokines In Excess-weight Pre...mentioning
confidence: 99%